Trinorlabdane diterpenoid alkaloids featuring an unprecedented skeleton with anti-inflammatory and anti-viral activities from Forsythia suspensa. Issue 47 (6th September 2021) - Li, Wei; Zhao, Lin; Sun, Li-Tong; Xie, Ze-Ping; Zhang, Shu-Min; Yue, Xi-Dian; Dai, Sheng-Jun
Abstract : Two unique trinorlabdane diterpenoid alkaloids, forsyqinlingines A (1 ) and B (2 ), were isolated from the ripe fruits of Forsythia suspensa, and found to show significant anti-inflammatory activities and anti-viral activities. Abstract : Two unique trinorlabdane diterpenoid alkaloids, forsyqinlingines A (1 ) and B (2 ), were isolated from the ripe fruits of Forsythia suspensa . Their structures, including absolute stereochemical configurations, were fully elucidated from extensive spectroscopy experiments, single-crystal X-ray diffraction, and electronic circular dichroism (ECD). In addition, a plausible biosynthetic pathway for the formation of compounds 1 and 2 in Forsythia suspensa was also proposed. In vitro, the two C17 -labdane diterpenoid alkaloids exhibited anti-inflammatory activities by inhibiting the release of β-glucuronidase in rat polymorphonuclear leukocytes (PMNs), and antiviral activities against influenza A (H1N1) virus and respiratory syncytial virus (RSV).